Potential endophytic bacteria from E. elatior’s roots for plant growth-promoting activities - Mohd Rosli, Norsalsabila; Ponari, Md Hoirul Azri; Meenakshi Sundram, Tamil Chelvan; Zainuddin, Zarina; Yunus, Muhamad Fahmi (UMT Press, 2025)
Plant Growth-promoting Endophytic (PGPE) bacteria contribute to various developmental processes such as nitrogen fixation, plant disease resistance, nutrient cycling improvement, and the production of plant hormones and enzymes. Etlingera elatior is a plant from the Zingiberaceae family that has been used for medicinal, bioactivities, ornamental, culinary, and floral arrangement purposes. Diverse microorganisms with unknown potential reside in the roots of E. elatior. However, research on the presence of PGPE and its plant growth-promoting activities is still green. Therefore, this study aims to isolate and characterise the beneficial endophytic bacteria with plant growth-promoting activities. Results showed that six bacteria were successfully isolated from the roots of the plant. These bacteria exhibit a positive activity for phosphate solubilisation, indole-3- acetic acid production, nitrogen, fixation, and plant growth-promoting properties. Three of the six endophytes with the best results were molecularly identified. The results of 16S ribosomal ribonucleic acid sequence analysis identified endophyte A3 as Enterobacter cloacae, endophyte A4 as Bacillus velezensis, and endophyte B2 as Bacillus siamensis. Endophyte A3 exhibited the highest phosphate solubilising activity, with an index value of 3.13±0.03. The isolated PGPE from this study demonstrated significant potential as plant growth-promoting amendments.